Moniezia benedeni drives CD3+ T cells residence in the sheep intestinal mucosal effector sites - Chai, Wenzhu; Yao, Wanling; Pan, Jing; Huang, Zhen; Wang, Baoshan; Xu, Bin; Fan, Xiping; He, Wanhong; Wang, Wenhui; Zhang, Wangdong (Frontiers in Veterinary Science, 2024)
T cells are the core of the cellular immunity and play a key role in the regulation of intestinal immune homeostasis. In order to explore the impact Moniezia benedeni (M. benedeni) infection on distributions of CD3 + T cells in the small intestine of the sheep. In this study, sheep pET-28a-CD3 recombinant plasmid were constructed and expressed in BL21 receptor cells, then the rabbit anti-sheep CD3 polyclonal antibody was prepared through recombinant protein inducing. The M. benedeni-infected sheep (infection group, n = 6) and healthy sheep (control group, n = 6) were selected, and the distributions of CD3 + T cells in intestinal laminae propria (LP) and mucous epitheliums were observed and analyzed systematically. The results showed that the rabbit anti-sheep CD3 polyclonal antibody had good potency and specificity. In the effector area of small intestine, a large number of CD3 + T cells were mainly diffusely distributed in the intestinal LP as well as in the mucous epitheliums, and the densities of intestinal LP from duodenum to jejunum to ileum were 6.01 cells/10 4 μm 2 , 7.01 cells/10 4 μm 2 and 6.43 cells/10 4 μm 2 , respectively. Their distribution densities in mucous epitheliums were 6.71 cells/10 4 μm 2 , 7.93 cells/10 4 μm 2 and 7.21 cells/10 4 μm 2 , respectively; in the infected group, the distributions of CD3 + T cells were similar to that of the control group, and the densities in each intestinal segment were all significantly increased (P < 0.05), meanwhile, the total densities of CD3 + T cells in duodenum, jejunum and ileum were increased by 33.43%, 14.50% and 34.19%. In LP and mucous epitheliums, it was increased by 33.57% and 27.92% in duodenum; by 25.82% and 7.07% in jejunum, and by 27.07% and 19.23% in ileum, respectively. It was suggested that M. benedeni infection did not change the spatial distributions of CD3 + T cells in the small intestine of sheep, but significantly increased their densities, which lays a foundation for further research on the regulatory mechanism of sheep intestinal mucosal immune system against M. benedeni infection.